2002
DOI: 10.1128/cdli.9.4.808-811.2002
|View full text |Cite
|
Sign up to set email alerts
|

Antigenicity of Leishmania braziliensis Histone H1 during Cutaneous Leishmaniasis: Localization of Antigenic Determinants

Abstract: The humoral immune response against Leishmania braziliensis histone H1 by patients with cutaneous leishmaniasis is described. For this purpose, the protein was purified as a recombinant protein in a prokaryotic expression system and was assayed by enzyme-linked immunosorbent assay (ELISA) with a collection of sera from patients with cutaneous leishmaniasis and Chagas' disease. The assays showed that L. braziliensis histone H1 was recognized by 66% of the serum samples from patients with leishmaniasis and by 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 20 publications
0
25
0
3
Order By: Relevance
“…Among them, CPA, Histone H1, KMP-11, and LeIF were found to be highly immunogenic as described in murine experimental models, cured VL patients and L. infantum infected dogs and have been considered as potential vaccine candidates (3941, 44, 45, 57). The induction of an effective T cell response against vaccine antigens requires antigen processing and peptide presentation by antigen-presenting cells (APCs), and it is well-established that T cells recognize the peptide sequence in association to appropriate MHC molecules.…”
Section: Discussionmentioning
confidence: 97%
“…Among them, CPA, Histone H1, KMP-11, and LeIF were found to be highly immunogenic as described in murine experimental models, cured VL patients and L. infantum infected dogs and have been considered as potential vaccine candidates (3941, 44, 45, 57). The induction of an effective T cell response against vaccine antigens requires antigen processing and peptide presentation by antigen-presenting cells (APCs), and it is well-established that T cells recognize the peptide sequence in association to appropriate MHC molecules.…”
Section: Discussionmentioning
confidence: 97%
“…The use of histones in the diagnosis of CL or ML is less studied. The presence of antibodies against L. peruviana rH2B [25] as well as against L. braziliensis H1 [56] has been detected in sera from CL patients. In the present study, we show that the recombinant histones are recognized by a moderate percentage of sera from ML or CL patients but also presented moderate cross reactivity with sera from patients from diseases other than Leishmaniasis, mainly by sera from SLE patients.…”
Section: Discussionmentioning
confidence: 99%
“…Intralesional isotype profiles in human localized cutaneous leishmaniasis lesions has been studied and it was shown that the predominant isotypes were IgG1 and IgG2 suggesting a preferential Th1 immune response (Aragort et al, 2001). Antibody response of human cutaneous leishmaniasis cases has been investigated for different antigens such as KMP-11 (Trujillo et al, 1999), CPA and CPB (Rafati et al, 2001) and Histone H1 (Carmelo et al, 2002). In addition, immunoblotting technique has been used to find antigen(s) for differential diagnosis of cutaneous leishmaniasis (Brito et al, 2001;Goncalves et al, 2002).…”
Section: Discussionmentioning
confidence: 99%